ENGLISH FOR SPECIFIC PURPOSES IN TOURISM EDUCATION: A SYSTEMATIC ANALYSIS OF PEDAGOGICAL TRENDS AND CURRICULUM GAPS - Bahagia Saragih; Ayu Lestari; Ameera Fadhillah; Najwa Kamila Harpan; Sefrina Anastasya Simbolon; Maharani Yasika; Aqsha Dinanti; Muthia Fitriani; Yohana Putri S. Simanjuntak; Priska Oktaviani Br Ginting; Gloria Pasca Simarmata; Tengku Hastridilla; Sarah Hendratno Simanjutak; Debora Jesika Sihotang, Putri Rohni Sitio (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the trends, gaps, and future directions of English for Specific Purposes (ESP) in tourism higher education.ESP in tourism is essential for preparing students to communicate professionally in global service contexts, yet many curricula still focus mainly on linguistic knowledge rather than authentic workplace communication. This study employed a qualitative descriptive design through a literature review of scholarly sources related to ESP, tourism education, hospitality communication, curriculum development, and professional communication. The findings show that tourism ESP instruction has shifted toward communicative, task-based, and scenario-based learning. However, gaps remain in students’ psychological readiness, willingness to communicate, intercultural competence, and ability to respond spontaneously in real service encounters. The study highlights the need for a holistic ESP curriculum that integrates linguistic competence, emotional preparedness, intercultural awareness, digital communication skills, and authentic workplace practices. Such integration can better prepare tourism students to become confident, adaptive, and professional service practitioners in international contexts.